2018
DOI: 10.2144/btn-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcodes from Snake Venom: a Broadly Applicable Method for Extraction of DNA from Snake Venoms

Abstract: DNA barcoding is a simple technique used to develop a large-scale system of classification that is broadly applicable across a wide variety of taxa. DNA-based analysis of snake venoms can provide a system of classification independent of currently accepted taxonomic relationships by generating DNA barcodes specific to each venom sample. DNA purification from dried snake venoms has previously required large amounts of starting material, has resulted in low yields and inconsistent amplification, and was possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Since the inception of the Cold Code (Che et al, 2012; Murphy et al, 2013), the effectiveness of making preliminary identifications of herpetofaunal species using DNA barcodes has been increasingly shown, and it has also accelerated the development of DNA barcoding of herpetofauna (Arida et al, 2021; Bernstein et al, 2021; Chambers & Hebert, 2016; Hawlitschek et al, 2016; Laopichienpong et al, 2016; Lyra et al, 2017; Mulcahy et al, 2018; Smith et al, 2018; Trivedi et al, 2016; Vacher et al, 2020; Zangl et al, 2020). Here, we provide a DNA barcode reference library for over 80% of recognized species of Chinese snakes and identify 36 candidate species that could not be assigned to any nominal species based on morphological characters (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inception of the Cold Code (Che et al, 2012; Murphy et al, 2013), the effectiveness of making preliminary identifications of herpetofaunal species using DNA barcodes has been increasingly shown, and it has also accelerated the development of DNA barcoding of herpetofauna (Arida et al, 2021; Bernstein et al, 2021; Chambers & Hebert, 2016; Hawlitschek et al, 2016; Laopichienpong et al, 2016; Lyra et al, 2017; Mulcahy et al, 2018; Smith et al, 2018; Trivedi et al, 2016; Vacher et al, 2020; Zangl et al, 2020). Here, we provide a DNA barcode reference library for over 80% of recognized species of Chinese snakes and identify 36 candidate species that could not be assigned to any nominal species based on morphological characters (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…For 42 species and one candidate species with multiple OTUs, maximum within-OTU genetic distances were much lower than the maximum intraspecific p-distance of the corresponding species and candidate species. Chambers & Hebert, 2016;Hawlitschek et al, 2016;Laopichienpong et al, 2016;Lyra et al, 2017;Mulcahy et al, 2018;Smith et al, 2018;Trivedi et al, 2016;Vacher et al, 2020;Zangl et al, 2020). Here, we provide a DNA barcode reference library for over 80% of recognized species of Chinese snakes and identify 36 candidate species that could not be assigned to any nominal species based on morphological characters (Table S1).…”
Section: Otu Delimitationmentioning
confidence: 99%
“…The presence of nucleosides in snake venom and its role in toxicity was documented but there was limited information on free nucleotides (4,5). However, it is known that snake venom contains ribonucleic acid (RNA) (63,64) and deoxyriboucleic acid (DNA) (65,66), which comes from the cells covering the lumen of the venom gland. In line with this information, it is highly possible that peaks originating from PO 2 -stretching vibrations in the FTIR spectrum arise mainly from nucleic acid backbone and nucleosides.…”
Section: Discussionmentioning
confidence: 99%
“…Besides rapid species identification, this approach is also performed to detect the Molecular Taxonomic Units (MOTUs) (Tyagi et al 2017(Tyagi et al , 2019. Further, this molecular tool is also successfully evident in forensic science by naming the unknown snakes from their venoms (Sharma et al 2016;Smith et al 2018). The earlier study suggested significant genetic divergence was observed in the different population of two deadly snakes in India and other adjacent countries (Ophiophagus hannah and Bungarus fasciatus) (Kundu et al 2020).…”
Section: Introductionmentioning
confidence: 99%